Pengaruh Gaya Kepemimpinan Terhadap Kualitas Kerja Tim (Teamwork Quality) - Della Nur Shayidah; Anniez Rachmawati Musslifah (International Forum of Researchers and Lecturers, 2024)
This study discusses the relationship between leadership style and the quality of teamwork in companies. This study uses literature review analysis to examine the concept of leadership style which includes authoritarian, democratic, and independent styles, as well as the concept of quality teamwork (TWQ). The results of this study show that the right leadership style and good relationship between leaders and employees can affect the quality of teamwork significantly. Effective communication and collaboration between team members are the most important factors in improving the quality of teamwork. Therefore, Companies are encouraged to pay attention to the leadership style of a leader and improve and teamwork to achieve goals and improve overall employee performance.